Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1172/jci143950
|View full text |Cite
|
Sign up to set email alerts
|

The druggable transcription factor Fli-1 regulates T cell immunity and tolerance in graft-versus-host disease

Abstract: Brief summary: Fli-1 regulates both inflammatory and anti-inflammatory T-cell subsets and can be targeted via available pharmaceutical agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Fli1 −/− studies demonstrated a down-regulation of genes associated with pro-inflammatory states, while genes with anti-inflammatory properties were up-regulated 79,80,82 . Additionally, metabolic pathways were also affected by FLI1 knockout in T cells, which displayed decreased glycolytic but increased oxidative phosphorylation activity 78 in line with our data. TCF7 is essential for a normal chromatin landscape in T cells 83 , acting mainly as a positive regulator on chromatin accessibility 39 and is critical for formation of long-term memory T cells 84 and Th17 longevity 38 .…”
Section: Discussionsupporting
confidence: 91%
“…Fli1 −/− studies demonstrated a down-regulation of genes associated with pro-inflammatory states, while genes with anti-inflammatory properties were up-regulated 79,80,82 . Additionally, metabolic pathways were also affected by FLI1 knockout in T cells, which displayed decreased glycolytic but increased oxidative phosphorylation activity 78 in line with our data. TCF7 is essential for a normal chromatin landscape in T cells 83 , acting mainly as a positive regulator on chromatin accessibility 39 and is critical for formation of long-term memory T cells 84 and Th17 longevity 38 .…”
Section: Discussionsupporting
confidence: 91%
“…Fli-1 promoted transcription of T-bet, RORγt in CD4 + T cells, but inhibited expression of activation-related genes and function-related genes within CD8 + T cells. 16 In bleomycin-treated Fli-1 +/− mice, the percentage of Treg cells from the dermis was decreased in relative to that in bleomycin-treated controls, but percentages of Th1, Th2, and Th17 cells did not markedly change between them. 12 Levels of GM-CSF was relatively low in Fli-1 +/− T cells, where Fli-1 directly binds to GM-CSF promoter.…”
Section: Impact Of Fli-1 On Immune Cellsmentioning
confidence: 83%
“…CD4 + Fli‐1 +/− T cells treated with Th1/Th17 polarizing‐conditions induced little proportion of Th1, Th17 cell. Fli‐1 promoted transcription of T‐bet, RORγt in CD4 + T cells, but inhibited expression of activation‐related genes and function‐related genes within CD8 + T cells 16 . In bleomycin‐treated Fli‐1 +/− mice, the percentage of Treg cells from the dermis was decreased in relative to that in bleomycin‐treated controls, but percentages of Th1, Th2, and Th17 cells did not markedly change between them 12 .…”
Section: Function Of Fli‐1 On Immune Cells and Non‐immune Cellsmentioning
confidence: 92%
“…6 D). Moreover, T5224 significantly inhibited camptothecin (CPT, an anti-FLI1 compound [ 20 , 41 , 42 ])-induced HEL apoptosis in culture (Fig. 6 E, F).…”
Section: Resultsmentioning
confidence: 99%